Dirshuni : Contemporary Women's Midrash - Biala, Tamar (Book collections on Project MUSE., 2022)
"Dirshuni: Contemporary Women's Midrash, is the first ever English edition of an historic collection of midrashim composed by Israeli women. The volume features a comprehensive introduction to Midrash for the uninitiated reader by the distinguished scholar Tamar Kadari and extensive annotation and commentary by Tamar Biala"--